RURAL POPULATION OF DAGESTAN IN 1920-1930S: HISTORICAL AND DEMOGRAPHIC ASPECT - Amirhanova, Madina Magomedovna (History, Archeology and Ethnography of the Caucasus, 2022)
The author reviews the demographic processes in the Dagestan village in one of the most dramatic periods of its history. The article aims to study the size, age and sex composition, migration processes, ethnic structure of the rural population based on the materials of the All-Union Census of 1926, 1937 and 1939. During the selection and classification of specific facts, the author strove for objectivity, relying on the principle of historicism, using comparative historical and logical research methods. The statistical method and the method of generalizing indicators made it possible to calculate the average statistical indicators of the natural and mechanical movement of the population. The analysis of the demographic situation in the Dagestan villages in the first twenty years of Soviet power made it possible to determine the positive dynamics of population reproduction; shows changes in the ratio of urban and rural population due to migration processes, while the urban population grew at a faster rate than the rural one; the changes observed in the national composition of the republic according to the 1939 census are revealed, in which many nationalities were united on the basis of linguistic kinship into groups under the common name “highlanders of Dagestan”. In addition, the census data demonstrate the desire of the republic’s leadership to artificially accelerate the spontaneous processes of consolidation of the peoples of Dagestan, their actual assimilation. In conclusion, the 1926 census recorded the natural increase of the villagers. Censuses 1937 and 1939 showed a positive mechanical growth of the villagers. However, natural growth remained the main channel for the reproduction of the population, which was facilitated by the improvement of socio-economic living conditions. The theoretical and practical significance of the work is determined by the expansion of scientific knowledge about the demographic situation in the Dagestan village, the population of which largely determined the development trends of the region during the period under study. When writing the paper, official documents of the republican Soviet and party bodies, survey materials of the Workers’ and Peasants’ Inspectorate of the DASSR, works of Russian social scholars, historians and economists were used.
Keywords: rural population; Dagestan; civil war; population size; All-Union Census; natural growth; mechanical growth; ethnic structure; migration